2016
DOI: 10.1016/j.jcyt.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

An approach to personalized cell therapy in chronic complete paraplegia: The Puerta de Hierro phase I/II clinical trial

Abstract: Personalized cell therapy with MSCs is safe and leads to clear improvements in clinical aspects and quality of life for patients with complete and chronically established paraplegia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 34 publications
5
62
2
1
Order By: Relevance
“…Intralesional transplantation of autologous MSCs in subjects with complete SCI is safe, is feasible, and may play some roles to promote neurological improvements [81, 82]. Consistently, an approach to personalized cell therapy in chronic SCI indicated that all patients experienced improvement, primarily in sensitivity and sphincter control, while intralesional motor activity, according to clinical and neurophysiological studies, obtained an improvement by more than 50% of the total 12 patients [83]. A case report indicated that MSC transplantation can partially promote recovery of deep sensory pathways as demonstrated by somatosensory evoked potential (SSEP) recording and alleviate neuropathic pain of a patient with traumatic complete cervical SCI [84].…”
Section: Function Of Msc Transplantation After Scimentioning
confidence: 99%
“…Intralesional transplantation of autologous MSCs in subjects with complete SCI is safe, is feasible, and may play some roles to promote neurological improvements [81, 82]. Consistently, an approach to personalized cell therapy in chronic SCI indicated that all patients experienced improvement, primarily in sensitivity and sphincter control, while intralesional motor activity, according to clinical and neurophysiological studies, obtained an improvement by more than 50% of the total 12 patients [83]. A case report indicated that MSC transplantation can partially promote recovery of deep sensory pathways as demonstrated by somatosensory evoked potential (SSEP) recording and alleviate neuropathic pain of a patient with traumatic complete cervical SCI [84].…”
Section: Function Of Msc Transplantation After Scimentioning
confidence: 99%
“…Tables 1-3 show the results of clinical trials using ASC transplantation (including one activated macrophage and two Schwann cell trials) in various phases of SCI according to the American Spinal Injury Association Impairment Scale (AIS). Although many SCI patients treated with ASCs showed no changes in terms of AIS, some studies reported improvements of two AIS grades (A→C or B→D) 1,14,23,26,27,34,40,45,47,51,59,64,67) . In addition, functional improvements such as walking 1,14,23,39,40,45,67) and bladder/bowel control 1,14,19,26,27,34,39,45,59,67) were used to reveal clinical change in several trials.…”
Section: Time Windows For Stem Cell Therapy In Scimentioning
confidence: 99%
“…In most of the clinical trials presented in Tables 1-3, researchers reported that their clinical trials were safe without mortalities or severe morbidities related to either procedures or transplanted cells. However, there were some reported complications which were not associated with the procedures or applied cells : fever 4,40,59,64) , urinary tract infection 2,19,27,59) , abnormal blood profiles 2,27,40,45) , transient hypertension 26) , vomiting 4,19) , pulmonary thromboembolism 27) , and general body ache 4) . On the contrary, some complications including transient neuropathic pain 2,26,27,29,37,67) , transient deterioration in sensorimotor symptoms 29,37,44,64) , cerebrospinal f luid leakage 67) , subarachnoid hemorrhage 67) and subcutaneous seroma 67) , might be related to stem cell delivering procedures.…”
Section: Safety Of Ascsmentioning
confidence: 99%
“…Cell survival and enhancement in locomotor performance have been observed both after intravenous injection of one million cells in a volume of 0.5 mL of DMEM in a model of balloon compressive injury in rats and after transplantation of 600,000 cells in a volume of 6 μL directly into the injury site after contusive injury in rats [112]. Other studies have advocated intrathecal administration from 100 × 10 6 up to 230 × 10 6 cells followed by an additional 30 × 10 6 cell administration at 3 months [5], or the administration of two or three intrathecal injections with a median of 1.2 × 10 6 mesenchymal stem cells/kg body weight [6]. In a phase III clinical trial, limited efficacy has been proven after injecting 1.6 × 10 autologous mesenchymal stem cells into the intramedullary area at the injured level and 3.2 × 10 autologous mesenchymal stem cells into the subdural space.…”
Section: Quantity and Numbermentioning
confidence: 99%
“…Mesenchymal stem cells, in particular, are easy to isolate, can be rapidly expanded in culture and can be cryopreserved without loss of potency [3,4]. Clinical reports on their use have varied, starting from documenting their safety [5,6] up to limited clinical efficacy [7], even partial or complete efficacy [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%